Temperature control of a PEM fuel cell test bench for experimental MEA assessment - Moré, Jerónimo José (2010)
This paper presents the design, implementation and testing of a temperature control for a laboratory PEM fuel cell stack work bench intended for evaluation of experimental MEAs.The controller design is based on a thermal model of the fuel cell stack developed by the authors. The model is extended to the complete temperature range by considering a nonlinear description of the heating resistances. Its parameters are experimentally adjusted and its accuracy is validated in all the temperature operating range. Then, the  temperature control is developed, using a proportional-integral structure with anti-windup  features. It is implemented in a PC connected to an ad-hoc equipment of acquisition and control, that drives distributed cycles actuators to energize two heating resistances. The controller proved to be capable of regulating the stack temperature in a wide operating range, while eliminating the ripple typical of ON-OFF actuators. Finally, experimental results of closed loop operation are presented, demonstrating the good performance of the proposed control set up and thermal model. ad-hoc equipment of acquisition and  control, that drives distributed cycles actuators to energize two heating resistances. The controller proved to be capable of regulating the stack temperature in a wide operating range, while eliminating the ripple typical of ON-OFF actuators. Finally, experimental results of closed loop operation are presented, demonstrating the good performance of the proposed control set up and thermal model.ad-hoc equipment of acquisition and  control, that drives distributed cycles actuators to energize two heating resistances. The controller proved to be capable of regulating the stack temperature in a wide operating range, while eliminating the ripple typical of ON-OFF actuators. Finally, experimental results of closed loop operation are presented, demonstrating the good performance of the proposed control set up and thermal model.